Information and Communication Technologies in Tourism 2021 2021
DOI: 10.1007/978-3-030-65785-7_47
|View full text |Cite
|
Sign up to set email alerts
|

“Nothing Can Stop Me!” Perceived Risk and Travel Intention Amid the COVID-19 Pandemic: A Comparative Study of Wuhan and Sapporo

Abstract: The global tourism industry has been devastated by the COVID-19 pandemic due to strict travel restrictions imposed by most countries. In order to achieve a swift post-pandemic recovery, it is important to understand what psychological obstacles people would face when making travel decisions. Building upon the dual-route theory of information processing, this study examined and compared how the perceived risk of COVID-19 would affect people’s travel intentions in the Japanese city of Sapporo and the Chinese cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 34 publications
1
29
0
2
Order By: Relevance
“…(From 2012 to 2014, Sanya's annual domestic overnight stays increased by 30.59%, 11.97%, and 11.33% [13], respectively; from 2015 to 2018, Qingdao's annual domestic overnight stays increased by 9.03%, 8.44%, 9.2% and 13.7% [14], respectively.) Empirical research has also found the negative impact of perceived risk on behavioral intention to be insignificant [15,16], or even found perceived risk to have a significant positive effect [17].…”
Section: Introductionmentioning
confidence: 99%
“…(From 2012 to 2014, Sanya's annual domestic overnight stays increased by 30.59%, 11.97%, and 11.33% [13], respectively; from 2015 to 2018, Qingdao's annual domestic overnight stays increased by 9.03%, 8.44%, 9.2% and 13.7% [14], respectively.) Empirical research has also found the negative impact of perceived risk on behavioral intention to be insignificant [15,16], or even found perceived risk to have a significant positive effect [17].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies investigating perceived risk and travel intentions have confirmed that risk perception is essential for travel decision making (Agyeiwaah et al, 2021;Falahuddin et al, 2020;Li & Ito, 2021;Zhan et al, 2020). When it comes to the differences between travel in the country and abroad in terms of risk perception, the findings indicate significant differences in terms of health risk, destination risk and travel risk.…”
Section: Discussionmentioning
confidence: 75%
“…Due to the health crisis caused by the COVID-19 virus, travel has been reduced and limited worldwide. The COVID-19 health crisis has destroyed tourism industry around the world, due to the travel limitations forced by most countries (Li & Ito, 2021). Tourism is certainly the most stricken sectors due the COVID-19 health crisis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the present study also contributes to the literature by shedding light on the relationship between perception of COVID-19 and job satisfaction. Because perception of COVID-19 has led to greater interest in airline research, several recent studies have focused on travelers perceptions of COVID-19 and how they impact travel intentions and willingness to fly ( Elizabeth et al, 2021 ; Lamb et al, 2020 ; Li and Ito, 2021 ; Neuburger and Egger, 2020 ; Xu et al, 2021 ). Nevertheless, how employees (e.g., airline staff) perceive the recent pandemic and how their perceptions influence job satisfaction remains understudied.…”
Section: Discussionmentioning
confidence: 99%